Medication prescription errors: an assessment of prescription in the pediatrics of a school hospital - DAYANE BESERRA COSTA; LUCIANA LUCENA ARANHA DE MACEDO; ROSA ÁGUIDA DONOSORA DE MELO SOUTO; ANA LUIZA DOS SANTOS (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2018)
The research aimed to analyze the quality of prescriptions in pediatrics with emphasis on prescription errors. This is an observational, descriptive, cross-sectional study with a retrospective design. It was performed in the Pediatric Clinic of a teaching hospital. The variables under study followed the recommendations of the Protocol of Safety in the Prescription, Use and Administration of Medications of the Ministry of Health. The data were stored, organized and statistically treated with the help of SPSS version 20 software. It were analyzed 898 prescriptions, and the following analyzed variables were absent: full name of the user 2.7%, patient number 61.5%, ward 1,2%, bed 80.5%, nursery 15,9%. The pharmaceutical form was absent in 26.1%, the drug concentration was not specified in 20.3% and the treatment time was not evidenced in 85.2% of the prescriptions evaluated. The volume and type of the diluent were not reported in 12.8% and 7.4% respectively, nor were 96.6% and 79.3% of the rate and time of infusion specified in the study prescriptions. The research shows that the quality of the prescription of the hospital in question needs major adjustments in several aspects, especially with regard to medicines. Key words: Patient safety, medication errors, pediatrics.